Pandangan Hakim Pengadilan Agama dalam Pelaksanaan Istbat Nikah terhadap Pernikahan Sirri yang Dilakukan Pasca Berlakunya UU No. 1 Tahun 1974: Studi Kasus Pengadilan Agama Stabat - Alvina Aliya; Muhammad Saleh; Ahmad Fuadi (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The term unregistered marriage is often heard by people to refer to a marriage that is carried out secretly and without being registered at the District Religious Affairs Office. For those who are Muslim, but cannot prove the marriage with a marriage certificate, they can submit an application for itsbat nikah (determination/validation of marriage) to the Religious Court as regulated in Article 7 Paragraph (3) of the Compilation of Islamic Law (KHI). This study aims to determine the Legal Procedure for Isbat Nikah for Unregistered Marriage, the differences in perspectives between religious law and state law regarding unregistered marriage, the obstacles faced by unregistered marriage couples in the marriage istbat process and to find out the views of religious court judges regarding istbat nikah for unregistered marriages carried out after the enactment of Law no. 1 of 1974 concerning marriage. The research method used in this study is a qualitative method. Qualitative methods are used to collect data and information from related sources, such as legal practitioners, judges, or couples who are unregistered. The marriage istbat process is a bridge to officially recognize unregistered marriages by the state, so that couples obtain the legal rights they should. With the coordination between these two legal systems, secret marriages can gain legal recognition, both before religion and the state. The view of religious court judges on the istbat nikah for secret marriages after the enactment of Law No. 1 of 1974 concerning Marriage reflects an effort to balance religious law that recognizes the validity of marriages according to religious requirements, and state law that requires administrative registration of marriages.